Big data for product innovation in manufacturing : evidence from a large-scale survey - Prester, Jasna (Array, 2019)
The article analyses big data usage in the Croatian manufacturing sector. Big data usage is still low but present. We analysed the influence of six sources of big data and their influence on share of returns generated by new products using two step OLS regression analysis. The results are robust but they show that some sources have positive and some have negative effects on share of returns generated by new products. Based on the most recent research of scholarly papers we define big data and show a clear research gap by linking big data and innovation. That is, only six papers deal with big data and innovation. In five papers big data comes from social media data, and in the remaining one paper they use data from sensors but predominantly to reduce cost or support the product. Therefore, we contribute by closing this research gap of linking big data and innovation.